Does early surgery result in improved long-term survival compared to watchful waiting in patients with asymptomatic severe aortic regurgitation with preserved ejection fraction?. (30th March 2022) - Heuts, Samuel; Kawczynski, Michal J; Maessen, J G; Bidar, Elham
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was: In patients with asymptomatic severe aortic regurgitation with preserved ejection fraction, is early surgery superior to watchful waiting in terms of long-term survival? Altogether, 648 papers were found using the reported search, 3 of which represented the best evidence to answer the clinical question (all level III evidence). The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. The 3 included studies comprised 469 patients. All 3 studies attempted to correct for potential baseline differences by different matching methods. As a result, a predominantly beneficial effect of early surgery on long-term survival in patients with severe asymptomatic AR and preserved LV function was observed, whereas none of the studies demonstrated a disadvantageous effect. Still, because many of the initially conservatively treated patients eventually proceed to surgery, longer term follow-up is warranted. Of note, older patients especially seem to adapt more poorly to chronic volume overload due to aortic regurgitation, making them potential candidates for a more aggressive approach. However, when a justified watchful waiting strategy is applied, close, extensive monitoring seems to be imperative, because the development of class I and II triggers seems to lead to improved survival. Abstract : A best evidence topic (BET) was constructed according to a structured protocol.